Commercial video games as a resource for mental health: A systematic literature review. Issue 12 (10th September 2022) - Boldi, Arianna; Rapp, Amon
ABSTRACT: Game-based interventions have been gradually and successfully implemented in the mental health domain given the games' ability to positively affect a variety of mental health conditions. To this aim, scholars have recently discovered the usefulness of Commercial Off-the-Shelf (COTS) video games, due to their increasing popularity, availability, and cost effectiveness. Nevertheless, key aspects of this line of research have not emerged yet, since a comprehensive overview of how commercial video games impact on different mental disorders is still missing. In this article, we present a systematic literature review of recent research that focuses on the usage of commercial video games in mental health. We analyse 39 papers and map the relevant themes that are recurrent in the last ten years of research, offering a detailed understanding of the methodological approaches that were used, the results obtained, the main disorders addressed, and the video game genres exploited. On the basis of these findings, we highlight open issues in current work and point out a variety of research opportunities that could be tackled in future years, like the need of conducting more field and longitudinal studies, the necessity of developing the design knowledge, and the possibility of connecting research with clinical practice.